Comparison of the effects of propranolol and ICI 66082 in blocking the renin releasing effect of renal nerve stimulation in the cat - Johns, E.J. (1974)
The comparative effectiveness of propranolol and ICI 66082, in inhibiting the release of renin from the kidney resulting from renal nerve stimulation, has been studied in the cat. Over the dose range 0.17-0.68 × 10(-5) mol/kg propranolol there was a dose-response relationship with the increase of plasma renin activity (PRA) achieved after 10 min stimulation. Over the dose range 0.75-1.69 × 10(-5) mol/kg ICI 66082 also inhibited the release of renin caused by nerve stimulation, but was about five times less effective than propranolol. It would appear from these data that the β-adrenoceptors within the kidney mediating renin release are distinctly different from those of the heart.